(11-√17)(11+√17) (√43-5)²+10(√43-0,2) 14(1+√31)+(7-√31)² (√2-√15)²+(√6+√5)² С обьяснением пжлст

(11-√17)(11+√17) (√43-5)²+10(√43-0,2) 14(1+√31)+(7-√31)² (√2-√15)²+(√6+√5)² С обьяснением пжлст
Гость
Ответ(ы) на вопрос:
Гость
(a-b)²=a²-2ab+b² (a+b)²=a²+2ab+b² a²-b²=(a-b)(a+b) (11-√17)(11+√17) =11²-(√17)²=121-17=104 (√43-5)²+ 10(√43-0,2)=66 1)  (√43-5)²=(√43)² - 2*5*√43 + 5²=43-10√43+25=68-10√43 2)  10(√43-0,2)=10√43 - 10*0.2 =10√43-2 3)  68-10√43 + 10√43-2=68-2=66 14(1+√31)+(7-√31)²=94 1) 14(1+√31)=14+14√31 2)  (7-√31)²=7² - 2*7*√31 + (²√31)=49-14√43+31=80-14√43 3) 14+14√31+80-14√43=14+80=94  (√2-√15)²+(√6+√5)²=28 1)  (√2-√15)²=(√2)² - 2*√2*√15 + (√15)²=2-2√30+15=17-4√30 2)  (√6+√5)²=(√6)² + 2*√6*√5 + (√5)²=6+2√30+5=11+2√30 3) 17-2√30+11+2√30=17+11=28
Не нашли ответ?
Ответить на вопрос
Похожие вопросы